Spending on K-12 Public Education: The Lebanese Case - Shal, Tarek (Advances in Social Sciences Research Journal, 2022)
The purpose of this paper was to examine the public spending on education in Lebanon, in order to make recommendations for executives to strategize this sector. This is a desk review paper that uses secondary resources, using rigorous criteria for document selection. The paper overviews the importance of spending on education and its relationship with the overall quality of education. It highlights the different factors affecting public spending peculiar to the Lebanese context, the various challenges confronting the Lebanese K-12 public education sector, and the spending of Lebanon on it. It provides recommendations for stakeholders and policy-makers on areas that require more attention in terms of spending.